Combining parallel pattern generation of electrohydrodynamic lithography with serial addressing. Issue 54 (3rd September 2018) - Boudoire, F.; Partel, S.; Toth, R.; Heier, J.
Abstract : Via different electrode addressing schemes in electrohydrodynamic lithography, different patterns were generated. Abstract : Electrohydrodynamic lithography (EHDL) is a parallel patterning process which typically makes use of topographically structured electrodes to guide pattern formation along areas of higher electrical field strength. The main driving force for pattern formation is an electrostatic pressure acting on a thin film polymer surface caused by a voltage applied between a top and bottom electrode. We here demonstrate that the principle can be applied using an addressable electrode composed of interdigitated fingers. Depending on the applied voltages, line patterns with different periodicities were fabricated. Our proof-of-concept experiments pave the way for a parallel pattern replication process where a serially addressed master is used. We complement the experiments by modelling the potentials across the electrodes and electrostatic forces acting on the polymer surface using different addressing schemes. Numerical simulations of the experimental setup pointed to some critical issues we experienced during the design of the experiments.